Divisive Refinement of Metal Fiber at the PM0.1 Classification Stage for PM0.5–0.1 Sampling with Nanosampler - Yuta Kurotsuchi; Kazuhiko Sekiguchi; Yohei Hayakawa (Aerosol and Air Quality Research)
Abstract Multi-component analysis of PM0.5–0.1 collected by Nanosampler II metal (Steel Use Stainless: SUS) wool fiber at the PM0.1 classification stage is challenging owing to difficulties in SUS wool fiber separation after collection. A 4-division (4D) cartridge was developed to enable quantitative analysis of multiple components by dividing the SUS wool fibers into four sections. The performance of the 4D cartridge was evaluated using sulfate ion concentrations of actual atmospheric particulate matter (PM). Observations using the 4D cartridge revealed that the relative standard deviation (RSD) of sulfate ions was lower for mesh with a large open area. In the case of the mesh with a large opening area, the partition did not block too much of the cross-sectional area of the SUS wool fiber, thus minimizing its effect on the airflow and possibly suppressing particle adhesion on the stainless-steel mesh. The PM0.1 classification efficiency test was conducted, and a linear analysis of the total filling mass of SUS wool fiber along with classifying efficiency of 100 nm PM was performed. In the 4D cartridge, it was estimated that 8.7 mg of SUS wool fiber was required to achieve a classification efficiency of 100 nm at 50% cutoff diameter because the apparent volume fraction of SUS wool fiber increases with the introduction of the partition. Using optimal mesh and amount of SUS wool fiber, the average RSD of sulfate ions was 5.6%, which was within the acceptable range (± 15%) for reanalysis of the Ministry of the Environment in Japan due to changes in analytical sensitivity of ionic components, confirming that PM was evenly collected from the four pieces of SUS wool fiber. This enabled multi-component analysis of all particle sizes including PM0.5–0.1 through the classified collection of PM using Nanosampler II.